2011
DOI: 10.3168/jds.2010-3736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a reduced-starch diet with or without exogenous amylase on lactation performance by dairy cows

Abstract: The objective of this trial was to determine lactation performance responses in high-producing dairy cows to a reduced-starch versus a normal-starch diet and to the addition of exogenous amylase to the reduced-starch diet. Forty-five multiparous Holstein cows, 68±29 d in milk and 696±62 kg of body weight (BW) at trial initiation, were randomly assigned to 1 of 3 treatments in a completely randomized design; a 2-wk covariate adjustment period with cows fed the normal-starch diet was followed by a 10-wk treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
59
0
5

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 27 publications
15
59
0
5
Order By: Relevance
“…A reduction (P = 0.04) in MUN was noted as dietary starch content increased, although the difference (13.3 mg/dL for HS vs. 14.6 and 14.8 mg/dL for LS and MS, respectively) was small and likely of little biological significance. Nonetheless, a lower starch diet (22 vs. 27% starch;Ferraretto et al, 2011) fed to cows of similarly high DMI and milk production (>26 kg/d of DMI and 45 kg/d of milk) also resulted in slightly lower MUN concentrations for cows fed lower-starch diets. Higher MUN for the LS diet compared with MS and HS diets may be related to a lower intake of starch that compromises ruminal microbial CP production (Oba and Allen, 2003).…”
Section: Lactation Performancementioning
confidence: 78%
See 2 more Smart Citations
“…A reduction (P = 0.04) in MUN was noted as dietary starch content increased, although the difference (13.3 mg/dL for HS vs. 14.6 and 14.8 mg/dL for LS and MS, respectively) was small and likely of little biological significance. Nonetheless, a lower starch diet (22 vs. 27% starch;Ferraretto et al, 2011) fed to cows of similarly high DMI and milk production (>26 kg/d of DMI and 45 kg/d of milk) also resulted in slightly lower MUN concentrations for cows fed lower-starch diets. Higher MUN for the LS diet compared with MS and HS diets may be related to a lower intake of starch that compromises ruminal microbial CP production (Oba and Allen, 2003).…”
Section: Lactation Performancementioning
confidence: 78%
“…However, previous studies are not in agreement with how starch content alters feed conversion and whether that is influenced by dietary ingredients. A recent study by Ferraretto et al (2011) observed decreased efficiency with decreased dietary starch, whereas Gencoglu et al (2010) found no effect of starch on efficiency, suggesting that animal responses may possibly differ with dietary ingredients and dietary starch content.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Longer term continuous-lactation trials (12 wk) comparing normal-and reduced-starch diets have reported similar or reduced milk yields, similar or greater DMI, similar or reduced milk protein, and similar or reduced feed efficiency (kg of milk yield/kg of DMI; Gencoglu et al, 2010;Ferraretto et al, 2011Akins et al, 2014) for cows fed corn-based, reduced-starch diets. Estimates of ruminal nutrient digestion and bacterial protein flow when reduced-starch diets are fed may help us better understand the effects of these feeding strategies and allow for dietary adjustments and improvements in animal performance.…”
Section: Introductionmentioning
confidence: 97%
“…Data were available on average daily feed intake per week from 447 primiparous and multiparous cows from 7 designed feeding experiments at the University of Wisconsin Emmons Blaine Dairy Cattle Research Center (Arlington, WI) and 3 designed feeding experiments at the USDA, Agricultural Research Service, Dairy Forage Research Center (Prairie du Sac, WI; Ferraretto et al, 2011;He et al, 2012). These experiments were conducted between October 2007 and March 2012.…”
Section: Wisconsinmentioning
confidence: 99%